AT işletmeleriyle bütünleşmede teknolojinin stratejik yönetimi - Akdemir, Ali (Anadolu Üniversitesi, 1991)
In this study basically, strategic management of technology has been studied for Turkish companies which reach to EC Companies in a competitive structure. Before this, a theoritical framework has been explained about the strategicof management of technoloji and various states have been determined. This study consists of eight parts. In the first part, the purposes, contents, hypothesiss, limitations and methodology of the study explained. In the second part, strategic dimentions of EC integration and Turkiye's expectations from EC membership has been explained in a micro and macro view. In the third part, comparative analyses of tecnological instutions, R+D personnel and expense levels of Turkiye and EC companies tookplace. This comparasion has been done both for countries and companies. The causes and basics of technological resurts has been sarched. In the fourth part, technological competitiveness level of EC- Turkish companies manufacturing sector classifactions have been analysed. The fifth part has involved the strategic management theoritical technology. This part has also been the theoritical framework at the sixth part. In the sixth part, opportunities and threats of EC membership and increasing of foreign investments and consume union have been explained. Then, technological strategies that will be fallowed by Turkish firms has been explained. The seventh part has involved explanation and evaluation of different dimentions technological states and R+D structure of different foreign and domestic companies which operate in Turkiye. In the eight past, a model for the establishment of collective sectional R+D centers has been seggested. The role of technoparks in the resional and sectional development and its efectiveness in universty-industrypublic cooperation has been explained. The study has been finished with application results and general results and suggestions.
Sadece dijital ortamda erişilebilir.
Keywords: A.T.; A.E.T.; İşletmeler